Conventional Spray-Drying and Future Trends for the Microencapsulation of Fish Oil - Gimenez-Castillo, B (Elsevier Ltd, 2016)
Polyunsaturated fatty acids, especially long-chain polyunsaturated omega-3 fatty acids (LCω3-PUFA), are essential in human nutrition because they play an important role in humans and prevent several diseases. Fish oil is a natural source of LCω3-PUFA that can be incorporated into food products. One of the major drawbacks of oils containing a high amount of LCω3-PUFA, such as fish oils, is their high susceptibility to oxidation and unpleasant flavours. Microencapsulation of fish oil by spray-drying has been proposed as a strategy to retard lipid auto-oxidation, improving oil stability, prolonging its shelf life, limiting the development of off-flavours and controlling the release into food. The encapsulation of fish oil by conventional spray-drying has been performed by preparing fish oil-in-water emulsions (micro- or nano-sized) by applying high shearing forces. The objective of this review is to compile the scientific research on the encapsulation of fish oil to discuss the main formulation and process variables that affect the physicochemical properties of the fish oil microparticles obtained by conventional spray-drying, the stability of fish oil during storage and the application of fish oil microparticles in food systems. An alternative strategy to conventional spray-drying (water-free spray-drying) is also proposed. © 2016 Elsevier Ltd